Fertility preservation rates among transgender women compared with transgender men receiving comprehensive fertility counselling. Issue 3 (September 2020) - Amir, Hadar; Yaish, Iris; Oren, Asaf; Groutz, Asnat; Greenman, Yona; Azem, Foad
Abstract: Research question: What is the fertility preservation rate among transgender women who have received professional fertility counselling compared with transgender men? Design: This retrospective cohort study included 56 transgender women and 56 transgender men referred for comprehensive fertility counselling at the Gender Clinic of the Tel Aviv Sourasky Medical Center's Fertility Institute between January 2017 and April 2019. Statistical analyses were performed to compare transgender men with transgender women who preserved fertility and transgender people who preserved fertility and those that did not. Results: The fertility preservation rate of transgender women was significantly higher than that of transgender men (85.7% versus 35.7%, respectively, P  < 0.001). The fertility preservation rate among transgender women was associated with being older and not having undergone gender-affirming hormone (GAH) treatment. The fertility preservation rate was higher among adolescent transgender boys compared with adolescent transgender girls (35% versus 6.25%, respectively, P  = 0.005). The duration of GAH treatment among the transgender men who preserved fertility was 70 months compared with 18.6 months for transgender women ( P  = 0.05). All transgender boys opted for oocyte cryopreservation, while half of the transgender men who had not started GAH opted for oocyte cryopreservation, and half of those who had already started on GAH opted for embryo cryopreservation. Conclusions: High fertility preservation rates among transgender individuals were found after comprehensive fertility counselling. Fertility preservation rates among adults were higher among transgender women compared with transgender men, while the opposite was found in transgender adolescents.